Holes in the Dike: The Global Savings Glut, U.S. House Prices and the Long Shadow of Banking Deregulation - Mathias Hoffmann; Iryna Stewen (Center for Economic Studies and ifo Institute (CESifo), 2015)
We explore empirically how capital inflows into the US and financial deregulation within the United States interacted in driving the run-up (and subsequent decline) in US housing prices over the period 1990-2012. To obtain an ex ante measure of financial liberalization, we focus on the history of interstate-banking deregulation during the 1980s, i.e. prior to the large net capital inflows into the US from China and other emerging economies. Our results suggest a long shadow of deregulation: in states that opened their banking markets to out-of-state banks earlier, house prices were more sensitive to capital inflows. We provide evidence that global imbalances were a major positive funding shock for US wide banks: different from local banks, these banks held a geographically diversified portfolio of mortgages which allowed them to tap the global demand for safe assets by issuing private-label safe assets backed by the country-wide US housing market. This, in turn, allowed them to expand mortgage lending and lower interest rates, driving up housing prices.
Keywords: G10; G21; G28; F20; F32; F40; 330; house prices; savings glut; global imbalances; credit constraints; state banking deregulation